Prediction and Identification of Covariates of Intra-cerebral Hemorrhage - Siddiqui, Afaq Ahmed; Cicchetti, Domenic V.; Wasay, M.; Khan, Rafeeq Alam; Yousuf Zai, M. Ayub Khan; Ahmed, Mansoor; Tabassum, Shagufta (International Journal of Statistics in Medical Research, 2015)
The authors investigate the effects of clinical covariates upon the outcome of Intra-cerebral Hemorrhage (ICH) patients by applying a discriminate model of logistic regression. About 985 patients’s data with ICH have been collected using the International classification of diseases; ninth revision codes are also included. Diagnostic codes (434 for stroke and 431 for ICH) were used to identify patients and confirmed by neuro-imaging of the patients using CT scan and MRI. A univariate analysis of 88 covariates was undertaken and 46 of them reached statistical significance at an acceptable level of p < 0.05. The multivariable analysis exhibited a significant negative relationship between ICH and hypertension. The improvement among ICH patients having hypertension was found to be 0.5 with the p=0.001, ARR=0.5, 95% C.I. 0.3 – 0.8. The development among ICH patients using antihypertensive medicine was 1.3 with p = 0.021, ARR=1.3, 95% C.I. 1.0 – 1.6. Thus present study manifested that ICH has strong relationship with use of antihypertensive medicine. The rate of perfection in the patients physiological conditions using antihypertensive medicine at the time of discharge was 2.9 times acquiring p < 0.001, ARR=2.9, 95% C.I. 2.7 – 3.2 as compared to those who could not use antihypertensive medicine. The change in ARR from 1.3 to 2.9 times depict that the exercise of antihypertensive medicine and ICH outcome are positively associated. The fluctuations in ARR of hypertensive range of systolic blood pressure (SBP) also indicate that the blood pressure range and ICH outcome are negatively correlated. The neurological symptomoatology, indistinct speech and double vision are important factors of proposed models. Moreover, a clear decrease was found in mental status from normal to coma in most suitable model. Surgery is an important part of recovery, and estimated that the improvement among the ICH patients, who were treated under surgical aspects, was 1.4 times with significant p-value in the best models. The complication of pneumonia during treatment of ICH subjects has highly significant showing negative correlation with the given outcome variable. The current model has 89.3% area under the curve with sensitivity (82.6%), specificity (81.3%) and p-value (0.308). This indicates that the constructed model bestows the well performance of the ICH outcome and the model is considered as excellent.